Effects of bacteriophage on inhibition and removal of mixed biofilm of enterohemorrhagic Escherichia coli O157:H7 and O91:H-. (December 2020) - Zhang, Yu; Shigemura, Kumiko; Duc, Hoang Minh; Shen, Cunkuan; Huang, Hung-Hsin; Sato, Jun; Masuda, Yoshimitsu; Honjoh, Ken-ichi; Miyamoto, Takahisa
Abstract: This study describes the characterization of bacteriophage FP43, active against pathogenic and non-pathogenic strains of Escherichia coli, and its ability to inhibit and remove a mixed biofilm of enterohemorrhagic E. coli O157:H7 and O91:H-. Phage FP43 is a member of the Myoviridae family, having a dsDNA genome consisting of 169, 248 bp with good stability. It has a short latent period and large burst size. Phage FP43 decreased the formation of biofilm, comprising E. coli O157:H7 and O91:H-, by 82.4% at 30 °C. After incubation for 6 h with FP43, viable counts of E. coli O157:H7 and total cells in the biofilm were reduced by 2.76 and 2.85 log, respectively. In planktonic cells, viable E. coli O157:H7 and total counts decreased by 3.44 and 3.62 log, respectively, after incubation with the phage for 4 h. Moreover, more than 60% of an established, mixed biofilm was removed after a 6 h exposure to the phage, in which E. coli O157:H7 and total viable counts decreased by 2.07 and 1.93 log, respectively. These results suggest that bacteriophage FP43 has broad host range against both pathogenic and non-pathogenic E. coli, and potential to reduce viable counts of both enterohemorrhagic E. coli O157:H7 and E. coli O91 in mixed-strain biofilm. Highlights: Lytic phage FP43 against both pathogenic and non-pathogenic E. coli was isolated and characterized. Phage FP43 inhibited mixed-biofilm formation of enterohemorrhagic E. coli O157:H7 and O91:H- strains. Phage FP43 can reduce risk of enterohemorrhagic E. coli infection through biofilm in food.